Attention deficit/hyperactivity disorder : a multidisciplinary approach - Holowenko, Henryk, 1955- (Jessica Kingsley, 1999)
Attention Deficit/Hyperactivity Disorder (AD/HD) is a medical diagnostic label for a mixed group of disruptive behaviours in children, which influences their development, family relationships and social interaction. AD/HD is part of a child's make-up: it is not a disease, but a pattern of problem behaviour, much of which is largely outside the sufferer's control. Attention Deficit/Hyperactivity Disorder: A Multidisciplinary Approach provides clear guidelines on good practice in assessment, diagnosis and management of, and provision for, children with AD/HD. Written for teachers, parents, medical practitioners, psychologists and other professionals, Holowenko's multidisciplinary approach stresses the collaborative nature of successful management of the condition. The book is based on the work of an interdisciplinary group whose aim was to identify a consensus view on the disparate positions on AD/HD.